2013
DOI: 10.1364/ao.52.006126
|View full text |Cite
|
Sign up to set email alerts
|

Stability and normal incidence reflectivity of W/B4C multilayer mirror near the boron K absorption edge

Abstract: A multilayer structure consisting of alternate layers of W and B4C has been deposited using a magnetron sputtering system. The structure of the as-deposited and vacuum-annealed W/B4C multilayer sample has been characterized using grazing incidence x-ray reflectivity, grazing incidence diffraction, and the normal incidence reflectivity has been measured using synchrotron radiation. A two-layer model consisting of tungsten and boron carbide is presented. The multilayer structure was found to be stable after 800°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Boron carbide is an important x-ray optical element in both hard and soft x-ray regions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Boron carbide is an important x-ray optical element in both hard and soft x-ray regions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar trend has been found in the W/B 4 C multilayers. The W/B 4 C multilayers experience an expansion of 1% after annealing at 500°C, the period thickness remains the same after annealing at 700°C and above [15].…”
Section: Introductionmentioning
confidence: 94%
“…W/B 4 C multilayers can form smooth interfaces and prove to be thermally stable. Reflectivity of 8% was obtained using W/B 4 C multilayer consisting of 50 bilayers at the 15°off normal incidence, while the measured reflectivity dropped 1% after 500°C annealing [15]. We have chosen the Mo/B 4 C multilayer bilayers in this study because B 4 C can form relatively smooth interfaces with Mo [16], and Mo/B 4 C has higher theoretical reflectivity compared to W/B 4 C multilayers within 6.6-7 nm wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ⁓11% reflectivity value of the as-prepared MoxC1-x/B4C multilayers made it less competitive in the choice of optical performance. Also, Rao et al [65] demonstrated a high thermal stable W/B4C PMMs after 800 °C annealing temperatures. They observed that there is no formation of tungsten carbide nor tungsten boride during the thermal treatments.…”
Section: Thermal Stability Of the Beuv Pmmsmentioning
confidence: 99%